A Multi-Organ-on-Chip Approach to Investigate How Oral Exposure to Metals Can Cause Systemic Toxicity Leading to Langerhans Cell Activation in Skin - Koning, Jasper J.; Rodrigues Neves, Charlotte T.; Schimek, Katharina; Thon, Maria; Spiekstra, Sander W.; Waaijman, Taco; de Gruijl, Tanja D.; Gibbs, Susan (Frontiers in Toxicology, 2022)
Investigating systemic toxicity in vitro is still a huge challenge. Here, a multi-organ-on-chip approach is presented as a typical case of topical exposure of oral mucosa to metals, which are known to activate the immune system and in turn may result in skin inflammation. Reconstructed human gingiva (RHG) and reconstructed human skin containing MUTZ-3–derived Langerhans cells (MUTZ-LC) in the epidermis (RHS-LC) were incorporated into a HUMIMIC Chip3plus, connected by dynamic flow and cultured for a total period of 72 h. Three independent experiments were performed each with an intra-experiment replicate in order to assess the donor and technical variations. After an initial culture period of 24 h to achieve stable dynamic culture conditions, nickel sulfate was applied topically to RHG for 24 h, and LC activation (maturation and migration) was determined in RHS-LC after an additional 24 h incubation time. A stable dynamic culture of RHG and RHS-LC was achieved as indicated by the assessment of glucose uptake, lactate production, and lactate dehydrogenase release into the microfluidics compartment. Nickel exposure resulted in no major histological changes within RHG or RHS-LC, or cytokine release into the microfluidics compartment, but did result in an increased activation of LC as observed by the increased mRNA levels of CD1a, CD207, HLA-DR, and CD86 in the dermal compartment (hydrogel of RHS-LC (PCR)). This is the first study to describe systemic toxicity and immune cell activation in a multi-organ setting and can provide a framework for studying other organoids in the future.